Analysis of the thermal behavior of the double skin envelope in the full scale testing modules of the postgraduate unit for a cloudy and a clear day / Ricardo Sanchez Benitez and Leonardo B. Zeevaert Alcantara - Ricardo, Sanchez Benitez; Leonardo, B. Zeevaert Alcantara (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
At the campus of the National Autonomous University of Mexico, on the roof of the “Jr” building of the Postgraduate Unit (19°18'33.59"N, 99°11 ’5.73"0), an Observation Deck and Experimentation Laboratory of the Master and PhD Program in Architecture are installed. This platform consists of two Full Scale Testing Modules. Each module has 9.00 m² of floor and 3.00 m high. The vertical envelope is formed by a double layer envelope with exterior and interior insulation. The horizontal envelope (cover) has insulation and a water proofing pre-manufactured system. The horizontal envelope (floor) has insulation outside and inside the structure as well as a radiation barrier. Data from each sensor was recorded every minute. The aim of this research is to characterize the thermal behavior of the Full Testing Modules;we are looking for thermalstability 24 hours a day. In order to do that, the first phase was to determine which of the measured variables directly affects the temperature of the innerside of the envelope. The obtained data was compared and showed that on a cloudy day, the global radiation does not interfere directly in the thermal behavior of the inner part. In this stage, the internal temperature of the module is directly related to the temperature inside the envelope. For a clear day we got that, the global radiation does interfere in the temperature of the innerface of the envelope, but is even more direct the relationship of the temperature inside the module with respect to the envelope temperature.